Impact of edema formation on functional outcome in pediatric stroke patients. (12th October 2022) - Sporns, Peter B.; Rusche, Thilo; Lee, Sarah; Hanning, Uta; Meyer, Lukas; Faizy, Tobias; Fiehler, Jens; Psychogios, Marios; Kemmling, Andre; Broocks, Gabriel
Abstract: Background: Quantitative lesion net water uptake (NWU) has been described as an imaging biomarker reflecting vasogenic edema as an early indicator of infarct progression. We hypothesized that edema formation measured by NWU is higher in children compared to adults but despite this functional outcome may be better in children. Methods: This study analyzed children enrolled in the Save ChildS Study who had baseline and follow‐up computed tomography available and the data were compared to adult patients. Results: Some 207 patients, of whom 13 were children and 194 were adults, were analyzed. Median NWU at baseline was 7.8% (IQR: 4.3–11.3), and there were no significant differences between children and adults (7.5% vs. 7.8%; p = 0.87). The early edema progression rate was 3.0%/h in children and 2.3%/h in adults. Median ΔNWU was 15.1% in children and 10.5% in adults. Children had significantly more often excellent (mRS 0–1; children 10/13 = 77% vs. adults 28/196 = 14%; p < 0.0001) and favorable clinical outcomes (mRS 0–2, 12/13 = 92% vs. 39/196 = 20%; p < 0.0001). Conclusions: In this study, clinical outcomes in children with large vessel occlusion strokes were better than in adults despite similar clinical and imaging characteristics and similar edema formation. This may be impacted by the generally better outcomes of children after strokes but may demonstrate that the degree of early ischemic changes using Alberta Stroke Program Early Computed Tomography Score (ASPECTS) and edema progression rate may not be a reason for exclusion from endovascular thrombectomy.